Vasculitis Retinae- A Rare Presentation of SLE (Anwer Khan Modern Medical College Journal, 2019)
Systemic lupus erythematosus (SLE) is a rare complex autoimmune disease characterized by autoantibody  formation against double strand DNA and antinuclear antibody (ANA), complement activation, and  deposition of immune complexes in tissues and organs. In normal population only 0.03% suffer from SLE,  among them 90% are female between the age of 20 to 30 yrs. SLE can involve any region of the visual  system. Although ocular manifestations are not part of the classification criteria for SLE but retinal involvement is the most common intraocular lesion observed in up to one-third of SLE patients. The most  common extra ocular lesion is keratoconjunctivitis sicca. Ocular manifestations are rarely reported at the  time of disease onset, but are usually associated with active generalized systemic disease. Due to low  frequency of SLE and only one third of them have ocular involvement, so reports about retinal vasculitis  are very rare. But fortunately a case of Vasculitis retinae due to SLE was admitted in Anwer Khan Modern  Medical College & Hospital on 04/12/2018Anwer Khan Modern Medical College Journal Vol. 10, No. 2: July 2019, P 179-182